Pretreating Callosobruchus maculatus (F.) eggs in mung bean with modified atmosphere conditions influence its adult emergence and survival. (March 2021) - Pascua, Glisten Faith S.; Bayogan, Emma Ruth V.; Salaipeth, Lakha; Photchanachai, Songsin
Abstract: Cowpea bruchid ( Callosobruchus maculatus Fab.) is a cosmopolitan pest that causes economic losses to legumes during storage. The present study determined the post-effects of exposing the C. maculatus eggs in mung bean to modified atmosphere (MA) conditions on the emergence and development of adults at ambient conditions (28 ± 3 °C and 65 ± 5% RH). The 24 h old C. maculatus eggs on mung bean kernel were packed with 500 g of mung bean in nylon/linear low-density polyethylene (nylon/LLDPE) bags (12.5 × 30 cm; 80 μm thick) and sealed with air (control), 100% CO2, 100% N2, and vacuum for 48 h. The very low O2 conditions in the MA package had significantly caused longer onset and developmental duration of egg to adult emergence and significantly reduced the adult emergence percentage of C. maculatus, especially those in the vacuum treatment. This was due to low pressure that disrupted the structure of the eggs as indicated by the scanning electron microscopy (SEM). In addition, the MA conditions shortened the adult emergence duration, longevity, and mortality duration. The number of females was also reduced by the low O2 conditions, particularly in those treated with vacuum. Eggs pretreated with the MA conditions probably affected the biomolecules of the eggs that in turn have affected the growth and development of the insect, with the order of effectivity highest in vacuum followed by 100% N2 then 100% CO2 . Graphical abstract: Image 1 Highlights: Pretreating bruchid eggs in mungbean to 100% N2, 100% CO2 and vacuum for 48 h. Disrupted egg structure was observed from those packed in vacuum by SEM analysis. Low oxygen concentration and low pressure affect physiological traits of adults. Onset and developmental duration were prolonged but shortened adult longevity. Number of adult emergence and females were reduced mostly by those packed in vacuum.